I Meningkatkan Frekuensi Menyusui Mempercepat Onset Laktasi - Nursanti, Ida (Universitas Jenderal Achmad Yani Yogyakarta, 2012)
Background: The administration of breast milk since early after birth is highly recommendedbecause it provides many health benefits for mother and baby. In the first hour, a baby willlearn to get used to sucking nipples and this prepares the mother to start producingcolostrums. The open access to maternal and infant closeness and unlimited frequency offeeding the baby for the first days after birth are the beginning of the acceleration of milkproduction. Objectives: To determine the postpartum mothers’ breastfeeding frequency, to determine theonset of lactation in primiparous postpartum mothers and to determine the effect ofbreastfeeding frequency on the onset of lactation on postpartum mothers in YogyakartaMunicipal Hospital. Methods: This was an observational study with a prospective cohort design. The number ofsamples was 54 determined purposively. The collection of data used observation sheet andchecklist. The study was started immediately after birth and followed until the third day. Thebivariable analysis used chi-square test with significant level of p <0.05 and CI95%.Results: The study found the majority of mothers had breastfed their babies with sufficientfrequency (72.2%) and with more rapid onset of lactation (64.8%) found in primiparouspostpartum mothers. There was a significant relationship between the frequency ofbreastfeeding and the onset of lactation, based on the analysis with p = 0.03, RR 2.3 andCI95% 0.95-4.23. Conclusion: Mothers who breastfed their babies with sufficient frequency were likely to havea 2.3 time opportunity to not delay the onset of lactation. Keywords: breastfeeding frequency, onset of lactation, primiparous